Mental Health and Psychiatric Nursing Clinical Handbook - Zabidah, Putit; Beatrice, Andrew Judin; Saptuyah, Baki (UNIMAS Publisher, 2020)
Mental health psychiatric nursing clinical handbook, the first clinical nursing handbook ever in Malaysia, is designed essentially for nursing student and medical student, paraclinical, medical practitioner, and those interested in mental health and psychiatric nursing. This handy book provides basic theory and practical insights into psychiatry. The book is crafted in a well-structured and easy to follow manual procedures with rationales.